Smoking Behaviors, Dietary Patterns, and Dyspepsia among Indonesian Adults in 2022 - Aprilawati, Dwi; Davis, Gerald Sebastian; Nuha, Muftihana Hanin; Ollyvia, Zsa Zsa; Fadilla, Aulia Nur; Rahmadanti, Ananda; Aufazhafarin, Nadhifa Tanesha; Kloping, Nabila Ananda; Priyambodo, Pamarga; Watang, Andreas Novaldi; Lumaksono, Nandiwardhana Dhira Pranaya; Munir, Sirazul (Universitas Airlangga, 2024)
Introduction: The global prevalence of dyspeptic syndrome among adults was estimated to be 1.8–57% in 2014, with an average of 20.8%. In a pilot survey involving 30 respondents, we found 21 acute respiratory infections, 16 dyspeptic syndromes, and 6 hypertension cases. Smoking was observed in 70% of the total respondents. This was the basis for conducting additional research in 2022 to examine the relationship between dyspepsia, smoking behaviors, and dietary patterns among adults in Krajan Hamlet, Malang, Indonesia. Methods: This quantitative study used an analytical observational design with a cross-sectional approach. The sample consisted of 70 adults aged 18–65, selected by random sampling. The collected data were analyzed using the Chi-squared test (p<0.05). Results: The prevalence rate for dyspepsia was 44.3%. Among them, 67.1% were smokers (both frequent and non-frequent), and 32.9% were non-smokers (including former and passive). The active smokers had a smoking duration of >2 years and smoked >10 cigarettes daily. A total of 11.4% of subjects exhibited eating habits of consuming trigger foods that put them at a high risk for dyspepsia. Specifically, 42.0% of subjects had an eating interval of >6 hours, while 87.1% had a meal frequency that led to a high risk of developing dyspepsia. There was a significant relationship between a high-risk diet and dyspeptic syndrome (p=0.037). Conclusion: High-risk diets exhibited a relationship with the prevalence of dyspeptic syndrome. Early detection is crucial in an effort to prevent and reduce the incidence and complications of dyspeptic syndrome. Highlights: 1. This study investigated the relationship between dyspepsia, smoking behaviors, and dietary patterns, which are often overlooked, particularly among those living in rural areas. 2. The findings of this study are anticipated to raise awareness regarding the detrimental impacts of smoking and unhealthy diets on dyspepsia.